Apoptosis regulation in adrenocortical carcinoma - Sofia S Pereira; Mariana P Monteiro; Sonir R Antonini; Duarte Pignatelli (Endocrine Connections, 2019)
Apoptosis evading is a hallmark of cancer. Tumor cells are characterized by having an impaired apoptosis signaling, a fact that deregulates the balance between cell death and survival, leading to tumor development, invasion and resistance to treatment. In general, patients with adrenocortical carcinomas (ACC) have an extremely bad prognosis, which is related to disease progression and significant resistance to treatments. In this report, we performed an integrative review about the disruption of apoptosis in ACC that may underlie the characteristic poor prognosis in these patients. Although the apoptosis has been scarcely studied in ACC, the majority of the deregulation phenomena already described are anti-apoptotic. Most importantly, in a near future, targeting apoptosis modulation in ACC patients may become a promising therapeutic.